Wissensintensive Unternehmensdienste als Motor des Produktivitätswachstums? Eine theoretische und empirische Bestandsaufnahme - Firgo, Matthias; Mayerhofer, Peter (Wirtschaft und Gesellschaft, 2017)
The starting point of this paper is the prominent hypothesis of negative effects on productivity and growth emanating from structural change towards services due to a minor potential for increases in efficiency in this sector. According to our results this hypothesis – at least for the NUTS-2-regions of Austria and the EU-27, respectively, and the time period analyzed (1991-2012) – has to be rejected. On the one hand this is because tertiarization has been driven by the growth of knowledge intensive business services (KIBS) since decades – an industry that in large parts is highly productive itself. On the other hand and above all our evidence reveals significant positive (direct plus indirect) total effects on regional productivity induced by KIBS on other industries due to their important role in creating knowledge-spillovers. Thus, our results call for economic policies grasping and strategically guiding the advancing structural change towards services, and fully exploiting the potential of KIBS as drivers of knowledge-spillovers and productivity dynamics. Thus, the article concludes with considerations on feasible policy measures supporting the development of KIBS in times of scarce financial resources.